ALTERNATIF UJI BEBAN PADA STRUKTUR (STUDI KASUS : JEMBATAN BAJA) - Soleh, Chairul; Rastandi, Josia Irwan (Universitas Tarumanagara, 2021)
The most common structural load test that has been widely used is the static load test. An alternative to the structural load test is dynamic load test. Dynamic testing is a test carried out to determine level of structural stiffness or structural elements stiffness in the form of natural frequencies, while the static load test is intended to obtain responses of static loading from the structure in the form of deflection. The discussion will emphasize the correlation between static load test and dynamic load test. To correlate the static load test with the vibration test, a reference or value that comes from modeling or theoretical analysis is needed. Structural modeling is carried out to obtain the theoretical natural frequency and the theoretical deflection which will then be compared with the natural frequency of the vibration test (dynamic). If the frequency of the test results and the theoretical frequency are compared to the theoretical deflection, the prediction of the test deflection will be obtained. The correlation between the predicted deflection of the test and deflection of the static load test is quite close with a difference of less than 12%. Judging from the above correlation, periodic inspections of the tested structures can be considered for vibration testing only. The types of structures reviewed are simple span steel bridge structure, simple span + link slab steel bridge structure and continuous span steel bridge structure. Keywords: modeling; natural frequencies; vibration testing; static load test AbstrakUji beban struktur yang umum dan sudah banyak dilakukan adalah uji beban statik. Alternatif lain dari uji beban adalah dengan melakukan pengujian vibrasi (dinamik) pada struktur. Pengujian vibrasi (dinamik) dilakukan untuk mengetahui tingkat kekakuan struktur atau elemen struktur berupa frekuensi alami, sedangkan uji beban statik dimaksudkan untuk mendapatkan respons hasil pembebanan statik dari struktur berupa lendutan. Pembahasan akan menekankan kepada korelasi antara uji beban statik dan uji beban vibrasi (dinamik). Untuk mengkorelasikan pengujian beban statik terhadap pengujian vibrasi (dinamik) diperlukan suatu acuan atau nilai yang berasal dari analisa pemodelan atau teoritis. Pemodelan struktur dilakukan untuk mendapatkan frekuensi alami secara teoritis dan lendutan teoritis yang kemudian akan dibandingkan dengan frekuensi alami hasil uji vibrasi (dinamik). Jika frekuensi hasil uji dan frekuensi teoritis dibandingkan terhadap lendutan teoritis maka akan didapatkan prediksi lendutan uji. Hasil korelasi antara prediksi lendutan uji terhadap lendutan uji beban statik cukup mendekati dengan perbedaan kurang dari 12%. Dilihat dari korelasi diatas, maka untuk pemeriksaan berkala pada struktur yang telah diuji dapat dipertimbangkan untuk dilakukan pengujian vibrasi saja. Jenis struktur yang ditinjau adalah struktur jembatan baja simple span, simple span + link slab dan continuous span.